(untitled) (Research, Society and Development, 2021)
The microorganisms found everywhere function in well-developed adaptive and reproductive abilities, making their spread wide. In the chosen school environment, children and adolescents of different age groups are chosen, this fact requires concern for the health and safety of students who are constantly exposed to pathological microorganisms related to poor hygiene habits, awareness of their own health and the form of hygiene of classroom desks. The study aims to characterize the most common microorganisms found in the school environment, proposing good practices that will inhibit their proliferation. It was carried out in two Public Schools in the State of Tocantins, located in the municipality of Guaraí, with classes in the 6th year of elementary school and 3rd year of high school. The collections were carried out in sanitized classrooms at the end of each shift, the first collection occurred before the beginning of the class and the second at the end, in 10 (ten) desks, totaling 40 entities, 20 from each room. The techniques used to carry out the study were observation of morphological characteristics of colonies of bacteria and fungi, Gram test, catalase, direct microscopic technique with potassium hydroxide (KOH). There was growth of bacteria and fungi in all school desks at the educational centers. It is evident the need for awareness of students about the proper hygiene habit, adequacy of the correct way of cleaning rooms and furniture in schools, to reduce the proliferation of microorganisms and consequently the risk of infectious diseases.